Armenia Travels the Bumpy Road to All-Day Electricity Supply : How Perseverance Pays Off in Power Sector Reform - Sargsyan, Gevorg; Balabanyan, Ani; Hankinson, Denzel (World Bank, Washington, DC, 2012)
Armenia's power sector has suffered many setbacks: in the late 1980s an earthquake that took its major nuclear plant off-line, and in the early 1990s the collapse of the Soviet Union, economic blockade, and repeated sabotage of a new gas pipeline-all of which severely disrupted fuel supply. The government set out to reform and privatize the sector, persevering through setbacks and learning from initial failure. Its persistence paid off: today the system runs efficiently and delivers power 24 hours a day. The following lessons can be learned from Armenia's example: Political will is paramount; champions matter; initial failure may be better than not trying at all; frequent, substantive communications with bidders helps; a comprehensive, cross-sectoral approach to reform is beneficial; reform should start before privatization; donors should provide the right mix of support; and service quality matters most.